The Implementation of Impromptu Speaking Method at Bilingual Boarding School - Dewi Sofiyanatiz Zahro; Januarius Mujiyanto; Dwi Rukmini (Dinasti Publisher, 2025)
This study explored the implementation of the impromptu speaking method in a bilingual learning environment at 10th Graders of MA Al-Musyaffa’ Semarang. The research aims to describe the assessment and the effectiveness of this method followed by the students’ perception toward this method. This study employed quantitative approach. The data were collected through pre-test and post-test, questionnaires, and documentation. The findings revealed that the assessment focused on fluency, vocabulary, pronunciation, and comprehension, with average students' pretest and posttest scores improving from 65.75 to 83.26. Furthermore, statistical analysis using SPSS Version 26 confirmed the effectiveness of this method, with a significant improvement in students' speaking skills (????-count = 7.671 > ????-table = 2.110, significance value = 0.00). The findings indicated a highly significant impact across all the speaking skill aspects. Additionally, students’ perceptions of the implementation of impromptu speaking method were categorized into positive and negative perceptions, comprised into personal, pedagogical, and activity-related factors.